Felidae from Cooper’s Cave, South Africa (Mammalia:Carnivora) - O'Regan, Hannah J.; Steininger, Christine M. (Muséum national d'Histoire naturelle, Paris, 2017)
The Cooper’s Cave System has produced a diverse fossil assemblage including the remains of Paranthropus robustus Broom, 1938, and early Homo. The majority of the faunal remains come from Cooper’s D, which dates to ~1.5 – 1.4 Ma. Here we describe 158 craniodental and postcranial felid fossils from Cooper’s D, including Dinofelis cf. aronoki. These fossils indicate the presence of four large felid genera at Cooper’s D: Dinofelis, Megantereon, Panthera (two species) and Acinonyx, plus two smaller taxa: Caracal and Felis. This assemblage may mark the first appearance of the modern cheetah Acinonyx jubatus (Schreber, 1775) in Africa, as well the first occurrence of the East African species Dinofelis cf. aronoki in southern Africa. This taxon appears intermediate in features between Dinofelis barlowi (Broom, 1937) and Dinofelis piveteaui (Ewer, 1955). We compare the Cooper’s D felid assemblage with those from other sites in the Cradle of Humankind, Gauteng, and discuss several scenarios for the evolution of the genus Dinofelis in eastern and southern Africa.